2020
DOI: 10.1097/mcp.0000000000000658
|View full text |Cite
|
Sign up to set email alerts
|

Occupational lung diseases in the 21st century: the changing landscape and future challenges

Abstract: Purpose of review Occupational exposures remain an underrecognized and preventable cause of lung disease in high-income countries. The present review highlights the emergence of cleaning-related respiratory disease and the re-emergence of silicosis as examples of trends in occupational lung diseases in the 21st century. Recent findings Employment trends, such as the shift from large-scale manufacturing to a service economy, the growth of the healthcare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Additionally, as a chronic inflammatory lung disease, silicosis shares some common pathogenic mechanisms with chronic obstructive pulmonary diseases (COPD) ( Beamer and Shepherd, 2013 ). Further, epidemiological studies have shown that patients with silicosis are prone to accompany with IPF and COPD ( Fazen et al, 2020 ; Walters, 2020 ). Identifying the shared and specific pathways that are modulated by the three diseases will contribute to a better understanding of the mechanisms underpinning silicosis progression.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, as a chronic inflammatory lung disease, silicosis shares some common pathogenic mechanisms with chronic obstructive pulmonary diseases (COPD) ( Beamer and Shepherd, 2013 ). Further, epidemiological studies have shown that patients with silicosis are prone to accompany with IPF and COPD ( Fazen et al, 2020 ; Walters, 2020 ). Identifying the shared and specific pathways that are modulated by the three diseases will contribute to a better understanding of the mechanisms underpinning silicosis progression.…”
Section: Introductionmentioning
confidence: 99%
“…During the recent outbreaks of silicosis across Australia since 2015, about 350 silicosis patients have been diagnosed, and many were characterized as accelerated silicosis (AS) which is more rapidly progressive than traditional chronic silicosis [ 2 ]. AS is caused by inhalation of high intensity of RCS from artificial or engineered stones which contain around 90% crystalline silica, much higher than natural stones such as marble and granite [ 3 ]. Compared with traditional silicosis, accelerated silicosis is characterized by severe alveolitis, collagen deposition, and a progressive clinical course that often results in death shortly thereafter [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Silicosis is the leading cause of BOD from pneumoconiosis [ 22 , 23 ]. From 1990 to 2019, the incident and prevalent cases of silicosis increased by 64.6% and 91.4% respectively, while DALY numbers only rose by 20.8%.…”
Section: Discussionmentioning
confidence: 99%